A REVIEW OF LITERATURE ON ENGLISH LANGUAGE PROFICIENCY TEST FOR PRE ENGLISH-TEACHER IN INDONESIA - Safitry, Tantri Sari (English Study Program, Faculty of Teacher Training and Educational Sciences, Universitas Timor, 2023)
A review of the current literature on English language test proficiency elucidates that much of the existing work either: (i) focuses on the scores of the proficiency test for more students and very few teachers, (ii) finds the correlation between the students' proficiencies with their studies at the campus, (iii) identifies the desirable competencies test to be applied to the students without providing any objective reasons why they need to have those competencies for mastering the English language. This paper scrutinizes the research development of English language test proficiency used for students and teachers, especially the pre-service teachers in Indonesia. Systematically, the article explores two essential aspects: the research development of English language test proficiency and English language test proficiency for pre-service teachers, both aspects focused on Indonesian contexts.